2008
DOI: 10.1016/j.biopsych.2008.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Orexin Mediates the Expression of Precipitated Morphine Withdrawal and Concurrent Activation of the Nucleus Accumbens Shell

Abstract: Background-The lateral hypothalamic neuropeptide, orexin (or hypocretin), is implicated in drug addiction. While a role for orexin has been shown in reward and dependence, the molecular and neural mechanisms are unclear. Here, we investigated the mechanism and neuroanatomical basis of orexin's role in morphine withdrawal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
79
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(94 citation statements)
references
References 58 publications
12
79
1
Order By: Relevance
“…or reported maximum effects at high doses (20-30 mg/kg i.p. ; Boutrel et al 2005;Harris et al 2005;Lawrence et al 2006;Richards et al 2008;Sakurai et al 1998;Sharf et al 2008). Brain levels of SB-334867 reach about 14 μM at only 10 mg/kg i.p., which should be more than enough for full effects in vivo, given its Ki of about 60 nM (Upton 2005).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…or reported maximum effects at high doses (20-30 mg/kg i.p. ; Boutrel et al 2005;Harris et al 2005;Lawrence et al 2006;Richards et al 2008;Sakurai et al 1998;Sharf et al 2008). Brain levels of SB-334867 reach about 14 μM at only 10 mg/kg i.p., which should be more than enough for full effects in vivo, given its Ki of about 60 nM (Upton 2005).…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that the orexin-1 receptor antagonist SB-334867 attenuates morphine-conditioned place preference (CPP) and reinstatement (Harris et al 2005(Harris et al , 2007Narita et al 2006), stressinduced cocaine reinstatement (Boutrel et al 2005); but see lack of effect of intra-VTA orexin-1 receptor blockade on stress-induced cocaine reinstatement (Wang et al 2009), cueinduced cocaine reinstatement ), cocaineinduced synaptic plasticity and sensitization (Borgland et al 2006), and intake and cue-and stress-induced reinstatement of ethanol (Lawrence et al 2006;Richards et al 2008;Sakurai et al 1998). In addition, SB-334867 attenuates precipitated morphine withdrawal (Sharf et al 2008) and nicotine self-administration (Hollander et al 2008). …”
Section: Introductionmentioning
confidence: 98%
“…The OX 1 receptor seems to mediate both the reinforcing and incentive motivational properties of opiates as systemic SB-334867 administration reduces operant selfadministration, progressive ratio breakpoint and cueinduced (but not drug-primed) reinstatement of heroinseeking [108]. SB-334867 also reduces morphine withdrawal in mice, suggesting OX 1 receptor involvement in this phenomenon [109]. No definitive role for the OX 2 receptor, however, has been established in opiate-seeking as yet.…”
Section: Orexin and Opiatesmentioning
confidence: 96%
“…It has been shown that chronic opioid administration in rodents promoted GABA-mediated excitation [14] and loss of neuronal inhibition via reduction of KCC 2 currents in the ventral tegmental area [15]. Furthermore, acute morphine withdrawal in rats increased c-Fos expression in dopaminergic neurons within nucleus accumbens shell in mice [16], and phosphorylation of NMDARs in the accumbens [17]. These studies imply that neuronal hyperexcitability within the limbic regions may alter activity within the dopamine-dependent motivation system, thus producing aversive effects to opioid withdrawal and reinforcing future drug seeking behaviors.…”
Section: Central Mechanisms Of Opioid Withdrawalmentioning
confidence: 99%